Análise da depreciação do forwarder com aplicação do custo anual uniforme equivalente - Simões, Danilo; Cervi, Ricardo Ghantous; Fenner, Paulo Torres [UNESP] (My University, 2013)
Depreciation is considered a necessary fixed cost to replace a machinery or goods at the end of its useful life thus interferingdirectly on the Equivalent Annual Cost (EAC). This paper aimed at analyzingdifferent methods used to calculate depreciation over the useful economic lifeof a Forwarder, a machine used ineucalyptus harvesting process, evaluating the influence of such methods inestimating EAC. Five depreciation methods were evaluated: Straight-line,Declining Balance, Sum-of-years-digits, Sinking Fund and InverseSum-of-years-digits. Results showed that Inverse Sum-of-years-digits reaches alower EAC for it provides a higher final value during the economic useful lifeof the Forwarder confirming that thechoice of the depreciation method may influence on the residual value of theassets over their economical useful lives.

A depreciação é considerada um custo fixo necessário para a substituição de uma máquina ou um bem ao final da vida útil econômica, a qual também infere diretamente sobre o Custo Anual Equivalente (CAUE). Este estudo teve como objetivo analisar diferentes métodos para o cálculo da depreciação durante avida útil econômica de um Forwarder, utilizado no baldeio de madeira de eucalipto, na prerrogativa de verificar a influência destes na estimativa do CAUE. Para a estimativa da depreciação, foram avaliadas cinco metodologias: Método Linear ou Linha Reta, Método Exponencial ou Saldo Decrescente, Método Somatório dos Dígitos Periódicos (Método de COLE), Método Fundode Renovação (Sinking Fund) e Método Somatório Inverso dos Dígitos Periódicos. Os resultados obtidos evidenciaram que, o método de depreciação do Somatório Inverso dos Dígitos Periódicos resulta em um menor CAUE, por proporcionar um maior valor final durante a vida útil econômica do Forwarder, corroborando que a escolha do método de depreciação pode influenciar no valor residual dos ativos ao longo de sua vida útil econômica. PALAVRAS-CHAVE:Avaliação econômica. Colheita florestal. Substituição de equipamentos.FORWARDER DEPRECIATION ANALYSIS APPLIED TO EQUIVALENT UNIFORM ANNUAL COST ABSTRACT Depreciation is considered a necessary fixed cost to replace a machinery or goods at the end of its useful life thus interferingdirectly on the Equivalent Annual Cost (EAC). This paper aimed at analyzingdifferent methods used to calculate depreciation over the useful economic lifeof a Forwarder, a machine used ineucalyptus harvesting process, evaluating the influence of such methods inestimating EAC. Five depreciation methods were evaluated: Straight-line,Declining Balance, Sum-of-years-digits, Sinking Fund and InverseSum-of-years-digits. Results showed that Inverse Sum-of-years-digits reaches alower EAC for it provides a higher final value during the economic useful lifeof the Forwarder confirming that
Custo anual uniforme equivalente
Keywords: Economic evaluation; Forest harvesting; Equipment replacement; Avaliação econômica; Colheita florestal; Substituição de equipamentos